Versi Pendidikan Nonformal dalam Pendidikan untuk Penanggulangan Pengangguran Muda Menurut Target SDG’s - Alim Harun Pamungkas (Jurnal Halaqah, 2020)
Someone who does not have an adequate educational background or skills only has the opportunity to be a laborer. If manual labor is no longer needed, it will potentially become unemployed. Skills education (vocational) which is obtained non-essential is important to enter the workforce. Education and skills can be a determinant of the future. A high educational background, but not enough skills can lead to difficulty finding a job. Conversely, ownership of skills, but don't have a formal educational background also has the potential to become unemployed due to high competition in the world of work. Ideally, young people must-have skills that are obtained informally and supplemented with adequate formal education so as not to become unemployed.